Women and ICTs: Raising awareness - Kipsang', Bett; Ouédraogo, Noelie Marceline (Technical Centre for Agricultural and Rural Cooperation, 2012)
Two projects, one in Kenya and one in Burkina Faso, show that female farmers have better access to ICTs and are using them to improve their livelihoods. However, there is still a gender digital divide, and some profound problems are preventing women from benefiting from ICTs